Unicystic ameloblastoma: 3 case reports and review of literature - Simi Thankappan; Valsa Thomas; Sharafudeen Kandamparambil; Sherin Nair (Wolters Kluwer Medknow Publications, 2008)
The term unicystic ameloblastoma (UA) refers to those cystic lesions that show clinical, radiographic, or gross features of a jaw cyst, but on histologic examination show a typical ameloblastomatous epithelium lining part of the cyst cavity, with or without luminal and/or mural tumor growth. Even though the lesion is not as aggressive as the solid ameloblastoma, an accurate histopathologic diagnosis is essential for the treatment and prognosis. Here we present 3 cases of UA showing different histologic features and coming under histologic variants of UA. These cases re-establish the fact that thorough microscopic examination of the surgical specimen is necessary for the final diagnosis of UA. Also the complexity of the diagnostic process of bone pathologies increases when the lesions are present at uncommon locations. The most important aspect governing treatment modalities in these three cases are individual considerations rather than theoretical factors.